Observational constraints on the kinetics of the ClO-BrO and ClO-ClO ozone loss cycles in the Arctic winter stratosphere - Butz, A.; Bosch, H.; Camy-Peyret, C.; Dorf, M.; Engel, A.; Payen, Sébastien; Pfeilsticker, K. (Geophysical Research Letters, 2007)
International audience Observations of the balloon‐borne LPMA/DOAS remote sensing instruments performed in the Arctic stratosphere in February 1999 are used to constrain a photochemical model. Measurements of all relevant nitrogen, chlorine, and bromine species indicate that moderate heterogeneous chlorine activation occurred in a filament of the Arctic vortex. Model‐measurement comparisons for OClO serve as an indicator of how well various scenarios of the involved reaction kinetics, in particular of the ClO‐BrO and the ClO‐ClO cycles, reproduce the observations. Recent suggestions for the photolysis rate of the ClO dimer, the equilibrium constant between ClO dimer and monomer, the rate of the ClO‐ClO association reaction, and the branching ratio of the ClO‐BrO reaction are consistent with the observations. Formation of an unstable isomer of ClONO2 cannot be reconciled with the observations. Modeled odd oxygen loss rates can be larger by 10% to 20% for the updated reaction kinetics compared to standard